A small drop of ink, falling like dew : an investigation into the process of interpreting the written word into an illustration : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University, New Zealand - McAuley, Michael (Massey University, 2008)
This investigation’s origin is one born of pragmatism. It seeks to improve the teaching and learning of illustration, a visual communication design discipline. The specific focus is text adaptation and the process involved in interpreting the written word into a visual image. Common characteristics of poor interpretation, identified after many years of teaching illustration, are the creation of images which are either based on relatively insignificant details from a text, or so removed from a text’s theme, that decoding an image’s intended meaning becomes extremely difficult. This study therefore seeks to provide insight into the process of interpreting written text into an illustration and offer some suggestions as to how novice illustration students can improve their skills in this process. The chosen methodology of this study is action research, and within a constructivistinterpretivist framework, work carried out with three groups of novice students, during three linked cycles of investigation has been analysed. Two separate, but linked learning strategies were developed incrementally. These can be thought of as thinking tools. The first one relates to comprehension of text while the second strategy focuses on analogical reasoning as an idea generation method. The data suggests that these learning strategies were successful, allowing students to develop more awareness of their design process and also create concepts which captured the essence of a text. This suggests that, while designing does involve tacit, intuitive thought, explicit methods of thinking can also assist design creativity. Much of the literature on design suggests that a paradigm shift is taking place within the field, in education as well as design practice. One of the characteristics of this change is a call for design educators to develop an epistemology of what constitutes design knowledge. This thesis is an addition to that ongoing search for understanding.
Keywords: Illustration study and teaching; Visual communication design; Fields of Research::330000 Education::330200 Curriculum Studies